Augmented Reality Pengenalan Bagian Tumbuhan untuk Siswa Sekolah Dasar Kelas 4: Augmented Reality Introduction to Plant Parts for Grade 4 Elementary School Students - Umbas, Williams; Tulenan, Virginia (Universitas Sam Ratulangi, 2024)
Abstract - Learning will be more easily understood and understood by students or students if it is supported by using learning media. The development of increasingly advanced technology, of course, affects various sectors of human life. This development plays a role in the development of a learning media. Learning media is becoming more interesting and more concise even though it does not reduce the essence of the material. One of the developments in learning media that is currently still new is learning media using Augmented Reality. The purpose of this study was to design and build an Augmented Reality introduction to plant parts for grade 4 elementary school students and this application runs on the Android operating system. This application is made using the Multimedia Development Life Cycle method. The result of this research is the application of augmented reality to introduce plant parts. It helps students to be more interesting in getting to know plant parts through information from several objects in 3D form. Keywords: 3D; Android; Augmented Reality; Learning ; Multimedia Development Life Cycle. Abstrak — Pembelajaran akan lebih dimengerti dan dipahami oleh peserta didik atau siswa apabila didukung dengan menggunakan media pembelajaran. Perkembangan teknologi yang semakin maju, tentunya berpengaruh kedalam berbagai sektor kehidupan manusia. Perkembangan ini turut berperan dalam perkembangan sebuah media pembelajaran. Media pembelajaran menjadi semakin menarik dan semakin ringkas meskipun tidak mengurangi esensi dari materi. Salah satu perkembangan media pembelajaran yang saat ini masih baru adalah media pembelajaran dengan menggunakan Augmented Reality. Tujuan penelitian ini adalah untuk merancang dan membangun Augmented Reality pengenalan bagian tumbuhan untuk siswa sekolah dasar kelas 4 dan aplikasi ini berjalan pada sistem operasi android. Aplikasi ini dibuat dengan metode Multimedia Development Life Cycle. Hasil dari penelitian ini adalah aplikasi augmented reality pengenalan bagian tumbuhan ini. siswa merasa terbantu lebih menarik untuk mengenal materi pengenalan bagian tumbuhan melalui informasi dari beberapa objek dalam bentuk 3D. Kata Kunci : 3D, Android, Augmented Reality, Multimedia Development Life Cycle, Pembelajaran.